Fern genomes elucidate land plant evolution and cyanobacterial symbioses. (July 2018) - Li, Fay-Wei; Brouwer, Paul; Carretero-Paulet, Lorenzo; Cheng, Shifeng; Vries, Jan; Delaux, Pierre-Marc; Eily, Ariana; Koppers, Nils; Kuo, Li-Yaung; Li, Zheng; Simenc, Mathew; Small, Ian; et al.
Abstract Ferns are the closest sister group to all seed plants, yet little is known about their genomes other than that they are generally colossal. Here, we report on the genomes ofAzolla filiculoides andSalvinia cucullata (Salviniales) and present evidence for episodic whole-genome duplication in ferns—one at the base of 'core leptosporangiates' and one specific toAzolla . One fern-specific gene that we identified, recently shown to confer high insect resistance, seems to have been derived from bacteria through horizontal gene transfer.Azolla coexists in a unique symbiosis with N2 -fixing cyanobacteria, and we demonstrate a clear pattern of cospeciation between the two partners. Furthermore, theAzolla genome lacks genes that are common to arbuscular mycorrhizal and root nodule symbioses, and we identify several putative transporter genes specific toAzolla –cyanobacterial symbiosis. These genomic resources will help in exploring the biotechnological potential ofAzolla and address fundamental questions in the evolution of plant life. The genomes of two fern species, Azolla filiculoides andSalvinia cucullata, are reported and provide insights into fern-specific whole-genome duplications, fern-specific insect-resistant gene evolution and fern–cyanobacterial symbiosis.